Victoria Kent: Solidarity and Editorial Commitment in the New York Exile - Bottai, Alessio (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2020)
This essay retraces in a concised way certain stages of Victoria Kent’s life, highlighting her commitment into the solidarity activities she did in the long time she was exiled, which started during the Spanish civil war. Her incredible work was spread through France, Mexico and United States. Victoria Kent’s story here is retraced with the goal to find a common ground between her political and cultural commitment during her exile. In particular, but not exclusively, it dwells on her exile in the United States, retracing her activities, her connections, friends and cultural projects. One of her most important works was the Ibéricamagazine in which, together with her partner Louise Crane, she put a lot of energy into. This lasted for over two decades, from 1953 to 1974.